(untitled) (Research, Society and Development, 2021)
Dental avulsion consists of a dentoalveolar trauma, in which the tooth is displaced out of the alveolo, and immediate treatment is the reimplantation of the avulsional dental element. Factors such as: extra alveolar time, storage medium, and the containment performed after dental reimplantation, are determinant in the favorable prognosis of the case. The aim of this article was to report the clinical case of avulsion of the upper central incisor. A 7-year-old male patient suffered a fall from his own height, causing avulsion of the dental element 11; four hours after the accident, with the element having been stored in dry medium, the reimplantation was performed and a rigid containment was made (Erich bar). In later care, the element in question was evaluated and the containment replaced by a semi-rigid one; reevaluated and referring for endodontic treatment. The case reported is an atypical case, for the clinical picture in question the factors mentioned were unfavorable for a good prognosis, however, the element that suffered avulsion and was reimplanted, is in function until the present moment, with 9 months of follow-up.